2021
DOI: 10.1177/0004867421998783
|View full text |Cite
|
Sign up to set email alerts
|

Learning from previous disasters: Potential pitfalls of epidemiological psychosocial research in the COVID-19 environment

Abstract: It is critical to understand the psychosocial impacts of the COVID-19 pandemic on populations around the world. In this article, we highlight the key challenges associated with epidemiological psychosocial research in a disaster context and reflect on lessons learned from firsthand experience over the last decade in Christchurch, New Zealand, following the 2010/2011 Canterbury earthquakes and 2019 Mosque attacks. We make recommendations for study design to improve the quality of research evaluating the impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…These comparisons broadly support the representativeness of the sample of New Zealand caregivers responding in the current research. Further, commentaries have highlighted a reliance on post-pandemic assessments as a key limitation of observational research methods assessing the psychosocial health impacts of COVID-19 ( Bell et al, 2021 ). The availability of longitudinal assessments of depression and anxiety in the 2018 and 2020 HWR surveys enabled the current study to provide context to cross-sectional associations between conditions of care and mental health outcomes following the initial COVID-19 restrictions in New Zealand, and represent a significant methodological step forward in understanding the impacts of components of the care role in the post-pandemic period, enabling differentiation of factors associated with existing vs increasing psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These comparisons broadly support the representativeness of the sample of New Zealand caregivers responding in the current research. Further, commentaries have highlighted a reliance on post-pandemic assessments as a key limitation of observational research methods assessing the psychosocial health impacts of COVID-19 ( Bell et al, 2021 ). The availability of longitudinal assessments of depression and anxiety in the 2018 and 2020 HWR surveys enabled the current study to provide context to cross-sectional associations between conditions of care and mental health outcomes following the initial COVID-19 restrictions in New Zealand, and represent a significant methodological step forward in understanding the impacts of components of the care role in the post-pandemic period, enabling differentiation of factors associated with existing vs increasing psychological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Many people worldwide are experiencing various changes and difficulties in a short period of time during the COVID-19 pandemic. Bell et al 34 insisted that it is important to understand the COVID-19 pandemic from a disaster perspective as well as its psychological implications. Indeed, a number of papers have reported that aside from the number of COVID-19 cases during the pandemic, a variety of people have also suffered psychological difficulties such as fear, depression, anxiety, and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…4 When examining the psychosocial impacts in a pandemic context, researchers experience key challenges not only with the choice of study design and measures but also in providing a multicultural perspective. 5 In this respect, researchers have obtained data using convenience 6 7 or representative sampling 8 by employing either cross-sectional 8 or longitudinal 7 9 design. Those studies have been carried out either on the general population [6][7][8] or on potentially vulnerable populations (such as the health workforce [10][11][12] or those with pre-existing risk factors such as having a previous history of mental disorders 9 13 14 ).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…When examining the psychosocial impacts in a pandemic context, researchers experience key challenges not only with the choice of study design and measures but also in providing a multicultural perspective 5. In this respect, researchers have obtained data using convenience6 7 or representative sampling8 by employing either cross-sectional8 or longitudinal7 9 design.…”
Section: Introductionmentioning
confidence: 99%